Financial constraints on sport organizations' cost efficiency: the impact of financial fair play on Italian soccer clubs. Issue 24 (21st May 2019) - Ghio, Alessandro; Ruberti, Massimo; Verona, Roberto
ABSTRACT: We analyze the effect of the introduction of stricter financial constraints on the trade-off between sporting and economic results. We apply a stochastic Cobb-Douglas production frontier model to a sample of Italian Serie A teams, i.e. first division, over the period 2005–2015 to evaluate the variation in soccer clubs' cost efficiency following the application of the UEFA Financial Fair Play (FFP) principles in 2010. FFP imposes stricter financial regulation as a requirement for a club to be admitted to Union of European Football Associations (UEFA) tournaments. Firstly, we find that FFP does not improve the average efficiency of the Italian first division teams. Secondly, we show that FFP has contributed to leveling the playing field, reducing the gap in terms of efficiency between top teams and lower-tier teams. Abbreviations: FFP: Financial Fair Play; UEFA: Union of European Football Associations; DEA: Data Envelopment Analysis; SFA: Stochastic Frontier Analysis